Turning priorities into feasible programs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Is the proceedings of a policy seminar on Agricultural Biotechnology for East and Southern Africa held in South Africa from 23 - 27 April, 1995. Edited by J Komen, J Cohen and Z Ofir 1996 179 pp ISBN 90 802544 2 8 produced by the Intermediary...